Alloionema californicum n. sp. (Nematoda: Alloionematidae): a new alloionematid from USA - Nermuť, Jiří; Půža, Vladimír; Mráček, Zdeněk; Lewis, Edwin (Zootaxa, 2016)
A new species of the family Alloionematidae was isolated from a rotten winged gourd at White Crane Garden, San Francisco, USA, sampled by Christopher Nelson in November 2010, and a live culture is deposited in Félix Lab Strain Database (http://www.justbio.com/worms/index.php), IBENS, Paris, France. Specimens from the culture have been examined. Both morphologically and molecularly, the nematode described herein as Alloionema californicum n. sp. differs from the other alloionematid species, A. appendiculatum and Neoalloionema tricaudatum. It is characterised by having a narrow stoma, 2.5–3.5 or 4 times longer than broad in adults or dauer juveniles respectively. Lateral fields are not present in adults but occur as one prominent ridge in dauers. Males have no bursa, six pairs of genital papillae and one single papilla. Dauers have large apparent phasmids in the middle of the tail. The ecology of the newly described species is unknown but probably it is a saprobic bacteriophagous nematode preferring rotting organic material.